Colloid-mediated fabrication of a 3D pollen sponge for oil remediation applications - Hwang, Youngkyu (2022)
There is tremendous interest in developing 3D scaffolds from natural materials for a wide range of healthcare, energy, photonic, and environmental science applications. To date, most natural materials that are used to make 3D scaffolds consist of fibril structures; however, it would be advantageous to explore the development of scaffolds from natural materials with distinct supramolecular structures. Herein, the fabrication of a mechanically responsive pollen sponge that exhibits tunable 3D scaffold properties and is useful for oil remediation applications is reported. By using pollen-based microgel particles as colloidal building blocks, the sponge fabrication process is optimized by tuning the processing conditions during freeze-drying and thermal annealing steps. Stearic acid functionalization transforms the pollen sponge into a hydrophobic scaffold that can readily and repeatedly absorb oil and other organic solvents from contaminated water sources, with similar performance levels to commercial, synthetic polymer-based absorbents and an improved environmental footprint.